2007
DOI: 10.1073/pnas.0707938104
|View full text |Cite
|
Sign up to set email alerts
|

HOXB13 promotes ovarian cancer progression

Abstract: Deregulated expression of HOXB13 in a subset of estrogen receptor-positive breast cancer patients treated with tamoxifen monotherapy is associated with an aggressive clinical course and poor outcome. Because the ovary is another hormone-responsive organ, we investigated whether HOXB13 plays a role in ovarian cancer progression. We show that HOXB13 is expressed in multiple human ovarian cancer cell lines and tumors and that knockdown of endogenous HOXB13 by RNA interference in human ovarian cancer cell lines is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(101 citation statements)
references
References 34 publications
3
93
0
5
Order By: Relevance
“…To study the pathophysiological relevance of early events of the metastatic cascade in human tumors, we selected highly metastatic MDA MB-231 breast cancer and low metastatic OVCAR 8 ovarian cancer cell lines (23,24). Interestingly, implantation of MDA MB-231 breast cancer cells in zebrafish embryos resulted in widespread tumor cell dissemination and metastasis at day 6 post-injection ( Fig.…”
Section: Hypoxic Metastasis Model In Zebrafishmentioning
confidence: 99%
“…To study the pathophysiological relevance of early events of the metastatic cascade in human tumors, we selected highly metastatic MDA MB-231 breast cancer and low metastatic OVCAR 8 ovarian cancer cell lines (23,24). Interestingly, implantation of MDA MB-231 breast cancer cells in zebrafish embryos resulted in widespread tumor cell dissemination and metastasis at day 6 post-injection ( Fig.…”
Section: Hypoxic Metastasis Model In Zebrafishmentioning
confidence: 99%
“…some tumors, aberrant Hox gene expressions directly drives tumorigenesis through escape from apoptosis [10], alterations to receptor signalling [11], tumor cell invasion [12], and epithelial-mesenchymal transition (EMT) [13].…”
mentioning
confidence: 99%
“…Most members of the HOX gene family are regarded as bidirectional regulation factors due to their tissue-specific expression and regulation (31). For example, HOXB13 was observed to be overexpressed in ovarian (32) and breast (33) cancer. Hwever, Jung et al (34) also reported that HOXB13 was downregulated in prostate cancer.…”
Section: No Of Patients Withmentioning
confidence: 99%